Krisis Identitas Diri pada Individu People Pleaser Generasi Z sebagai Ide Penciptaan Karya Ilustrasi Digital Bergaya Surealisme - Nadia Destyana Putri; Mujiyono Mujiyono (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Identity crisis among Generation Z people pleasers is a psychological phenomenon influenced by the need for social acceptance, environmental pressures, and the tendency to conform to social expectations. This condition may lead to identity confusion, emotional exhaustion, and blurred boundaries between the self and the social environment. Although this phenomenon has been widely discussed in psychology and represented in visual artworks, its visualization through surrealist digital illustration remains relatively limited. This creation aims to produce surrealist digital illustrations that represent social pressure, emotional conflict, validation needs, and loss of self-control among Generation Z people pleasers. The visualization employs a symbolic surrealist approach using digital painting techniques. The creative process consists of pre-production, production, and post-production stages, while the theme and visual concepts were developed through literature studies and references to surrealist artworks. The results consist of four digital illustration works entitled “What They Wanted”, “What Remained”, “What I Watered”, and “What Was Never Mine”, which represent the sequential stages of identity crisis, ranging from social adaptation, identity erosion, and emotional exhaustion to the loss of self-control. The aesthetic quality of the works is achieved through the combination of visual metaphors in the form of human figures, everyday objects, flora, and fauna that are transformed into surreal forms, combined with form distortion, color harmony, and irrational yet meaningful object relationships, creating a reflective and interpretative aesthetic experience while functioning as an effective medium of visual communication.